Application of Biotechnology in Coconut (Cocos nucifera L.): Sri Lanka (Plant Tissue Culture and Biotechnology, 2015)
With the growing of world population and industrialization there is rising demand for coconut?based health and beauty products. The producers might not be able to keep up this demand with the law production of coconut due to the land area under cultivation has declined from around 444,000 hectares to about 394, 840 hectares between 2000 and 2012 and the aging trees in coconut trees. So there is an urgent need for shifting to investigate how the use of recently developed biotechnological techniques can benefit the coconut industry. Here the describes recent utilization of (a) molecular markers, diversity and genetic improvements, (b) molecular detection and diagnosis of diseases; and (c) in vitro propagation in Sri Lanka and the future potential of biotechnology on the coconut industry.Plant Tissue Cult. & Biotech. 25(1): 103-116, 2015 (June)